Environmental Land Use Planning - Appiah-Opoku, Seth (IntechOpen, 2012)
Environmental Land Use Planning brings together leading scholars in the field of environmental problem solving to examine environmental problems and effects on land uses; analytical methods and tools in the field; and the role of governments, community grants and tradable permits in environmental planning. The chapters are based on empirical research from countries around the globe including Canada, USA, China, Nigeria, Germany, Serbia, Venezuela, and Brazil. The book discusses such issues as predicting changes in land use pattern, ecological footprint analysis, socioeconomic and behavioral modeling, and flood control approaches. It is insightful and serves as an important resource and reference material on environmental management.